MEMAHAMI DAN MENDESKRIPSIKAN HUBUNGAN NEGARA HUKUM DENGAN HAM - Hutama Hutabarat, Dany Try; Wahyuni, Ade; Amalia Vada, Dela; Anuary Sitorus, Eko; Efrianti Nasution, Rizka; Widia Astuti, Yuni (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
Human rights on the one hand by the concept of natural law is an inherent right of every individual human being since birth, but on the other hand the legality of human rights must be shaped by the flow of positivism. The debate over whether human rights should be stipulated in the constitution also influence the discussion of the UUD 1945. Finally, the UUD 1945 amendments regulate the basic rights of citizens more fully starts from the premise that human rights protection is an important element in the concept of a constitutional state. Incorporated therein also setting mechanism of "judicial review" in the Constitutional Court as a means to avoid any legislation contrary to the fundamental rights of citizens as guaranteed in the constitution.